2006
DOI: 10.1200/jco.2006.24.18_suppl.3037
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR2 blockade in patients with solid tumors: Mechanism of hypertension and effects on vascular function

Abstract: 3037 Background: Hypertension is the most common side effect in trials with inhibitors of vascular endothelial growth factor (VEGF) signaling, although the underlying pathophysiology is unclear. As the use of anti-VEGF therapy is increasing, hypertension and related serious adverse events are likely to become more important. Methods: To better understand this pathophysiology,blood pressure and vascular function parameters were assessed in this substudy of a phase I trial in patients with advanced solid tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Афлиберцепт и рамуцирумаб подавляют неоангиогенез за счет связывания рецепторов VEGFR1 и VEGFR2 [19]. Нефротоксичность антиангиогенных препаратов проявляется АГ, протеинурией и снижением СКФ, которые обусловлены системной эндотелиальной дисфункцией, тромботической микроангиопатией (ТМА) и подоцитопатией [21][22][23][24].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Афлиберцепт и рамуцирумаб подавляют неоангиогенез за счет связывания рецепторов VEGFR1 и VEGFR2 [19]. Нефротоксичность антиангиогенных препаратов проявляется АГ, протеинурией и снижением СКФ, которые обусловлены системной эндотелиальной дисфункцией, тромботической микроангиопатией (ТМА) и подоцитопатией [21][22][23][24].…”
Section: Discussionunclassified
“…через 8 нед лечения отмечено нами почти у 1/2 пациентов, что несколько выше, чем по данными литературы. Например, наиболее часто (42,4%) АГ вызывает афлиберцепт, другие препараты показывают меньшую частоту развития АГ: при лечении рамуцирумабом -21%, бевацизумабом -23,6% [21][22][23].…”
Section: Discussionunclassified
“…Hence, blockage of VEGF would lead to vasoconstriction [ 29 31 ]. Vascular rarefaction has also been hypothesized as a mechanism of hypertension induced by anti-VEGF therapy [ 32 ]. Hypertension may also reflect a renal parenchymal disorder (i.e., acute renal injury, glomerulopathy, and thrombotic microangiopathy) ( Figure 1 ).…”
Section: Renal Adverse Effectsmentioning
confidence: 99%
“…Hypertension is a common, mechanism-based effect of VEGF-signaling-pathway (VSP) inhibitors. Prior investigations suggested that blood pressure (BP) might be a valid, quantitative biomarker of VSP inhibitor pharmacodynamic effects ( 1 – 7 ). Several more recent studies have found that patients who develop hypertension with VSP inhibitor treatment have better progression-free and overall survival than those who do not ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%